Die kerkreg en kerkregering van die Nederduitse Gereformeerde Sendingkerk (1881-1915) - Plaatjies-Van Huffel, Mary-Ann (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
The church polity and church governance of the Dutch Reformed Mission (1881-1915) One can discern five church polity principles in this article to adjudicate the church polity and church governance of the Dutch Reformed Mission Church (DRMC): 1. The autonomy of the local church, 2. The character of the denominational ties, 3. The character of the power of the major assemblies, 4. The power to discipline church officials, 5. The right to appeal with regarding to the decisions of the major assemblies, This article deals cursorily with the church polity development of the Dutch Reformed Mission Church (1881-1915). The foundational grounds and main notions on Doleantie Church polity are being drawn upon in this article. The Doleantie did not try to develop a new church polity system, but is rather a regression to a system of church polity as enacted by the National Synod of Dordrecht (1618-1619). The Doleantie church polity (oud kerkrecht) impacted the church polity and the church governance of the DRMC.